(untitled) (Third Sector Social Economic Review, 2024)
This study examines health inequality and polarization in Turkey from a socioeconomic class perspective. The analysis uses data from the 2018 World Values Survey, which includes 2,145 observations. Socioeconomic indicators such as income, education, occupation, employment status, gender, marital status, and age were used for the analysis, and new inequality and polarization measures like Allison-Foster, Abul-Naga-Yalcin, and Cowell-Flachaire were applied because they are suitable for ordinal data. The findings reveal that health inequalities are more pronounced in groups below the median income level. In particular, individuals aged 65 and older, as well as low-income groups, are the most affected by health inequalities. Retired and unemployed men face greater difficulties accessing health services, while inequalities are less pronounced in professional and managerial occupations. Education level is also a significant factor, with inequalities being lower among highly educated individuals and higher among those with low education. These findings highlight the close relationship between health inequalities and socioeconomic factors. Low-income and elderly individuals experience serious challenges in accessing health services. Therefore, it is emphasized that health policies need to be reviewed within a framework of fairness. Developing effective social and economic policies, increasing the accessibility of primary health services, and addressing socioeconomic inequalities in Turkey are of great importance.